Bioimaging of thiazolidine-4-one-based new probes, fluorimetric detection of Cu2+ “on-off” sensor property, DFT calculation, molecular docking studies, and multiple real samples application - Karakiliç, Emel; Başçeken, Sinan; Eskiler, Gamze Güney; Uzuner, Uğur; Baran, Arif (Food chemistry, 2025)
Thiazolidinones have been the subject of various research areas for their biological activities, thus they were promising scaffolds to develop new drug agents. A novel thiazolidine 4-one-based fluorescent chemosensor probes PS (thiazolidine) and BO (oxazolidine) were designed and synthesized. Both probes showed specific recognition against Cu2+ via a “turn-off” fluorescence response in ACN/H2O (v/v: 50/50) stock solution (10 mM, pH = 7.0) with a detection limit of (for BO: 1.9 nM and PS: 1.03 nM). Finally, the detection of chemosensory PS and BO showed positive potential for the determination of Cu2+ in real food samples, drinking water, and mung beans. The compounds were characterized by diferent chemical and spectroscopic methods. The proposed binding mode for PS and BO with Cu2+ was confirmed by DFT calculation, and also they elucidated by bioimaging studies against MCF-7 live cell lines. Additionally, the docking experiment was performed on XylE and hAChE targets. •Novel sensors with high fluorescence emission based on thiazolidin-4-one have been developed.•BO and PS sensors showed high selectivity and “turn-off” detection for Cu2+.•Both BO (1.9 nM) and PS (1.03 nM) have low detection limits.•Both BO and PS exerted excellent cell-permeability and potentially responded to changes of Cu+2 in MCF-7 cells.•The applicability of both sensors to multiple real samples was determined.